Application of Agile Method in Web-Based Accounting Information System Innovation to Support Decision Making at Canisius Foundation Surakarta Branch - Krisnata, Fransiskus Adrian; Nugroho, Agus Cahyo; Koeswoyo, G. Freddy (Soegijapranata Catholic University, 2024)
Canisius Foundation Surakarta Branch is a non-profit organization engaged in education and located in Solo, Central Java. The Foundation is facing serious challenges in terms of receiving financial reports from schools and accounting recording processes that have not been standardized. Currently, the foundation still relies on Excel files sent by schools every semester, which slows down the managerial decision-making process. Due to these conditions, this research proposes the development of an Accounting Information System at the Canisius Foundation Surakarta Branch using the Agile method, specifically Feature-Driven Development (FDD). In this research, the system is designed by providing a unified financial report format and standardized standards for the accounting and transaction recording process. The Agile FDD method is used to ensure the development of a system that is fast, adaptive, and in accordance with the needs of the Foundation. It is expected that the designed system will help the Canisius Foundation Surakarta Branch to improve the foundation's operational efficiency, accelerate managerial decision-making, and produce more accurate financial reports. This research integrates modern technology with the accounting needs of educational foundations in accordance with applicable regulations, namely ISAK 35, and can be a foundation for the development of similar systems in other institutions.